Managing Cool-Season Weeds in Sugarbeet Grown for Biofuel in the Southeastern United States. (21st May 2018) - Johnson, W. Carroll; Webster, Theodore M.; Grey, Timothy L.; Luo, Xuelin
Abstract: Sugarbeet, grown for biofuel, is being considered as an alternate cool-season crop in the southeastern U.S. coastal plain. Typically, the crop would be seeded in the autumn, then grow through the winter and be harvested the following spring. Labels for herbicides registered for use on sugarbeet grown in the traditional sugarbeet production regions do not list any of the cool-season weeds common in the southeastern United States. Field trials were initiated near Ty Ty, GA, to evaluate all possible combinations of ethofumesate applied PRE, phenmedipham+desmedipham applied POST, clopyralid POST, and triflusulfuron POST for cool-season weed control in sugarbeet. Phenmedipham+desmedipham alone and in combination with clopyralid and/or triflusulfuron effectively controlled cutleaf eveningprimrose, lesser swinecress, henbit, and corn spurry when applied to seedling weeds. Ethofumesate PRE alone was not as effective in controlling cool-season weeds compared to treatments containing phenmedipham+desmedipham POST. However, ethofumesate PRE applied sequentially with phenmedipham+desmedipham POST improved weed control consistency. Clopyralid and/or triflusulfuron alone did not adequately control cutleaf eveningprimrose. Triflusulfuron alone effectively controlled wild radish. In the 2013–2014 and 2014–2015 seasons, December-applied POST herbicides did not injure sugarbeet. However, in the 2015–2016 season POST herbicides were applied in late October. On the day of treatment, the maximum temperature was 25.4 C, which exceeded the established upper temperature limit of 22 C for safe application of phenmedipham+desmedipham, and sugarbeet plants were severely injured. In the southeastern United States, temperatures frequently exceed 22 C in early autumn, which may limit phenmedipham+desmedipham use for controlling troublesome cool-season weeds of sugarbeet in the region. Weed control options need to be expanded to compensate for this limitation.